The Effect Of Audit Characteristics And Tax Aggressiveness On Indonesian Banking Companies - Fegato Arumdapta Ersudewo; Mahameru Rosy Rochmatullah (Yayasan Riset dan Pengembangan Intelektual, 2026)
The increasing demand for transparency and accountability in the banking sector has highlighted the importance of effective audit mechanisms in controlling corporate tax behavior. This study aims to examine the effect of audit characteristics, consisting of auditor industry specialization, audit tenure, and prior-year audit opinion, on tax aggressiveness among banking companies listed on the Indonesia Stock Exchange (IDX) during 2021–2025. This research employed a quantitative causal approach using secondary data obtained from annual reports and independent audit reports. The sample was selected through purposive sampling, and the collected data were analyzed using IBM SPSS through descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results show that auditor industry specialization and prior-year audit opinion have significant effects on tax aggressiveness, while audit tenure has no significant effect. Auditor industry specialization is associated with higher tax aggressiveness, whereas prior-year audit opinion contributes to reducing aggressive tax practices. Simultaneously, audit characteristics significantly influence tax aggressiveness, with an adjusted R² value of 24.4%. These findings indicate that audit mechanisms play an important role in shaping corporate tax behavior, although other factors beyond the research model may also influence tax aggressiveness.